(untitled) (INNOVATIVE ECONOMY, 2025)
Burbelo N.O., Kovshova I.O. THE BASIC PRINCIPLES OF FORMING FHWS-MODELS OF MANAGEMENT OF CONSULTING COMPANIES Purpose. This study aims to investigate the fundamental principles for developing FHWS (Flexible Hybrid Workspace Solution) management models within consulting companies amid contemporary global challenges. It seeks to identify the key factors influencing the successful implementation of FHWS models in consulting firms, as well as to formulate recommendations for the effective integration of these models into business processes. Methodology of research. The article applies methods of comparative analysis, a systematic approach, and content analysis of recent publications and research in the field of consulting company management, such as reports from McKinsey, Deloitte, PwC, Gartner and others. The research is based on the analysis of practical cases from consulting firms implementing hybrid work models. Findings. The study showed that FHWS models can significantly increase business process flexibility, reduce operating costs, and improve employee engagement through the ability to work from anywhere. At the same time, key challenges have been identified, such as coordinating remote teams, maintaining corporate culture, and ensuring information security. Originality. For the first time, the main types of hybrid company management models were systematized according to various characteristics and a comprehensive analysis of FHWS management models in the context of consulting companies was carried out, taking into account their specific needs and risks. New challenges and opportunities arising from the introduction of hybrid work formats are investigated and the main mechanisms for choosing a model in the company’s practical activities are substantiated. Practical value. The research findings can be utilized by consulting company managers to enhance management efficiency and optimize work processes. They are also valuable for developing strategies to integrate FHWS models into business processes to reduce costs and increase productivity. Key words: FHWS model, hybrid management, consulting companies, remote work, flexible workspaces, productivity, corporate culture.